IMPROVING CHILDREN'S VISUAL SPATIAL INTELLIGENCE THROUGH DRAWING AT BALI STREET MUMS AND KIDS PROJECT FOUNDATION, DENPASAR - Sumadewi, Komang Trisna; Yupardhi, Toddy Hendrawan; Primatanti, Putu Asih; Harkitasari, Saktivi (Community Development Journal, 2024)
Presently, multiple educational options exist for both primary school and higher education. The entire education system is designed to assist students in cultivating a range of abilities or intelligences inherent in each individual, encompassing mental and physical aspects. This concept is usually referred to as "Multiple Intelligences." Spatial visual intelligence is a form of intelligence that can visualize objects and possesses cognitive benefits in processing information through mental imagery. The parenting style employed by parents also influences children's intellectual ability. Based on interviews with foundation managers, it has been seen that due to online learning, youngsters affiliated with the foundation end up reverting to life on the streets, resorting to begging. Before the COVID-19 outbreak, the charity organized various programs and training sessions to enhance street children's skills. Several measures are implemented to diminish the inclination of street children to return to the streets. Nevertheless, given the prevailing circumstances, these activities have significantly reduced, resulting in children reverting to the streets as beggars, often with the consent of their parents. The foundation management anticipates providing training programs to cultivate children's intelligence, encompassing cognitive and emotional aspects. Furthermore, the foundation management seeks to provide parental education to parents of these youngsters. A service program was implemented to address these issues. It involved providing parenting education and teaching children how to draw to enhance their visual-spatial intelligence. The practice yielded a 60.4% increase in parents' knowledge and improved children's drawing skills. All participants attended this activity without exception. Therefore, this service program action was successful.